(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2016)
The paper shows the results of a research about the rehabilitation, expansion and correction of the Northeast Railroad, which covers the route from Belencito, in Nobsa Boyaca, to Bogota. With several visits the state of the railway was observed. Data was collected about the index of accidents, morbidity, and mortality. Further information was obtained about the average daily traffic variation in different points along the route. The first results are presented about the evaluation of these variables and their changes.